Level Kompetensi Digital Mahasiswa Pada Bidang Pemecahan Masalah - Sari, Nila Kartika; Budiarto, Mega Teguh; Ekawati, Rooselyna (SJME (Supremum Journal of Mathematics Education), 2023)
This study aims to identify the level of digital competence of Tribhuwana Tunggadewi University students in the area of problem solving. The research subjects were eight mathematics education students in the third and fifth semesters. Data on the digital competency level of the subject was obtained from the results of the mathematical problem solving test, observations during work, and subject interviews. The results showed that the average digital competency level of mathematics education students was at level 3 – 6, and there were no mathematics education students at level 1, 2, 7, or 8.